The Influence of Sharia Supervisory Board Characteristics on the Financial Performance of Islamic Banks - Malik, Hudan Baihaqi; Irfan Akmaludin; Hamid Asayesh (Journal of Islamic Economics Perspectives, 2024)
This study aims to analyze the influence of the characteristics of the Sharia Supervisory Board (DPS) on the financial performance of Islamic Banks. The research focus includes variables such as DPS size, DPS educational qualifications, number of DPS meetings, DPS reputation, bank size, and bank age. The data used are financial statements and DPS profiles of Islamic Commercial Banks (BUS) during the 2016-2020 period. Literature study and content analysis methods are used to collect and analyze data from previous studies. The results showed that DPS size has a significant negative effect on Return on Assets (ROA), while DPS educational qualifications have a significant positive impact on ROA. The number of DPS meetings has no significant effect on financial performance, and the DPS reputation variable also has no significant effect on ROA. In contrast, bank size and bank age have a significant positive impact on the financial performance of Islamic banks. These findings provide a deeper understanding of the factors that may affect the financial performance of Islamic banks, with implications for the improvement of corporate governance and related policies in the Islamic banking sector. Suggestions for future research include further analysis of contextual factors and risk management policies that may moderate the relationship between DPS characteristics and financial performance.